If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x = 32 + -2x Solving 6x = 32 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 6x + 2x = 32 + -2x + 2x Combine like terms: 6x + 2x = 8x 8x = 32 + -2x + 2x Combine like terms: -2x + 2x = 0 8x = 32 + 0 8x = 32 Divide each side by '8'. x = 4 Simplifying x = 4
| 40=18x-10x | | -3(x+5)+5x=10 | | 10x^2+7x-5=0 | | 6+x=32-x | | 9x-x=40 | | 5x+2(x+8)-6(4x-5)= | | -3x^2+7x=-10 | | 8xy+6yz-4xz-8xy= | | -47-18=13a | | -1(z-6)=-20 | | -7+8x=19x+15 | | -p=2 | | -6x+9=3x-27 | | (y+3)(y+5)= | | (3b^3+9b^2-3)+(2b^3-9b+7)= | | (15-7)x=(11+5)x | | -9=9(y+3) | | 3x+4(2-x)=4x+5 | | 4(2x)=72 | | (x^3+x^2+x+1)(5x-3)= | | 2(3+4)-6=48 | | 6x+4=24 | | 2(4x)=40 | | 9x-7+2x=8x+5-5x | | -x^2-x+2=0 | | (7x+5)(5x^2+8x+6)= | | 16x=-48 | | 0.8w-0.6+0.3w=3 | | (x^2-3x+4)(2x-1)= | | 6x+4= | | 7x+8x=105 | | 4(w-5)=12 |